2018
DOI: 10.3892/mco.2018.1558
|View full text |Cite
|
Sign up to set email alerts
|

MAGE-A9 in head and neck cancer: Prognostic value and preclinical findings in the context of irradiation

Abstract: Abstract. Radiotherapy alone, or as an addition to surgery is important for the treatment of head and neck squamous cell carcinoma (HNSCC). In addition to their expression in germ cells, melanoma associated antigens-A (MAGE-A) are only expressed in malignant tissue. Notably, there is a known correlation between MAGE-A9 expression and poor prognosis in HNSCC patients. However, current knowledge regarding the function of MAGE-A9 expression, particularly in the context of irradiation, is limited. MAGE-A9 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…MAGEA9 is considered to be a negative prognostic marker in various cancers [ 24 ]. Our study revealed that miR-143-3p directly targets and inhibits MAGEA9 expression.…”
Section: Discussionmentioning
confidence: 99%
“…MAGEA9 is considered to be a negative prognostic marker in various cancers [ 24 ]. Our study revealed that miR-143-3p directly targets and inhibits MAGEA9 expression.…”
Section: Discussionmentioning
confidence: 99%